Preoperative informed consent for mandibular third molar surgeries: A survey analysis in a subset of dentists and oral surgeons in Saudi Arabia - Mohammed Alkindi (Elsevier, 2019)
Objectives: The objective of this study was to identify patterns of obtaining preoperative informed consent from patients undergoing mandibular third molar surgeries, in a subset of general dentists and oral surgeons in Saudi Arabia, and to compare the consenting patterns based on the clinician's rank, years of experience, place of work and gender. Methods: A prospective questionnaire based study was designed and data was obtained through an online survey from 102 participants who were selected for the study. Demographic information, clinician experience, type of informed consent obtained and information related to discussion of legal implications and complications were collected. Descriptive analysis of the obtained data and statistical comparisons using cross tabulation and Pearson Chi-Square test with a 95% significance level (P < 0.05) were done between the independents demographic variables and dependent variables pertaining to patterns of preoperative consenting. Results: The survey response rate was 81.3% (n = 83), with 59.04% general dentists and 40.96% oral surgeons. The ratio of male to female respondents was approximately 3:1. Majority of the respondents reported a clinical experience of less than 10 years (77.11%) and were reportedly working in the private sector (73.49%). Nearly 80% of the respondents (79.52%) mentioned obtaining preoperative consent for mandibular third molar surgeries and was significantly higher (p-value - 0.018) among clinicians with more than 5 years of experience (90%). While 38.5% of the respondents indicated obtaining both a written and verbal consent, 53.01% obtained only a verbal consent. Majority of the respondents were aware of the legal implications of obtaining informed consent (81.93%) and disclosed incidental complications to their patients (91.57%). However, differences in the perceived post-operative complications associated with mandibular third molar surgeries were observed between general dentists and oral surgeons. Conclusion: The results of this study indicate a good level of knowledge about informed consent for mandibular third molar surgery and its legal implications among the dentists and oral surgeons who were surveyed. However, to avoid painful medico-legal disputes, a written informed consent signed by patients along with a witness should be considered mandatory. Keywords: Informed consent, Ethical standards, Mandibular third molar surgery, Dental malpractice